The role of mycorrhizal associations in plant potassium nutrition - Garcia, Kevin; Zimmermann, Sabine D. (Frontiers in Plant Science, 2014)
Potassium (K+) is one of the most abundant elements of soil composition but its very low availability limits plant growth and productivity of ecosystems. Because this cation participates in many biological processes, its constitutive uptake from soil solution is crucial for the plant cell machinery. Thus, the understanding of strategies responsible of K+ nutrition is a major issue in plant science. Mycorrhizal associations occurring between roots and hyphae of underground fungi improve hydro-mineral nutrition of the majority of terrestrial plants. The contribution of this mutualistic symbiosis to the enhancement of plant K+ nutrition is not well understood and poorly studied so far. This mini-review examines the current knowledge about the impact of both arbuscular mycorrhizal and ectomycorrhizal symbioses on the transfer of K+ from the soil to the plants. A model summarizing plant and fungal transport systems identified and hypothetically involved in K+ transport is proposed. In addition, some data related to benefits for plants provided by the improvement of K+ nutrition thanks to mycorrhizal symbioses are presented.